Frequency of Hyperhomocysteinemia in Young (≤45 years) patients presenting with Acute Ischemic Stroke - Naeemullah Bullo, Aaisha Aziz, Munir Afzal, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of hyperhomocysteinemia in young (≤ 45 years) patients presenting with acute ischemic stroke at Tertiary Care Hospital, Karachi. Methodology: The cross-sectional study was conducted at Department of Neurology and Medicine, Jinnah Postgraduate Medical Center Karachi from 1st February 2021 to 31st July 2021. Patients' data was collected after a verbal consent was obtained. The diagnostic criteria were met by 119 cases. Results: Mean age, duration of acute ischemic stroke, body mass index, height, weight and homocysteine level were 38.41±4.58 years, 6.54±3.91 hours, 28.66±3.51 kg/m2, 151±10.25 cm, 71.8±11.69 kg and 10.7±3.42 µmol/L. Fifty four (45.4%) and 65 (54.6%) were male and female. Fifty nine (49.6%) and 60 (50.4%) had and did not have hyperhomocysteinemia. Conclusion: 49.6% of young stroke patients had hyperhomocysteinaemia, a modifiable risk factor for ischemic stroke. Therefore close monitoring of patients must be done in all patients with regular follow-up. Keywords: Acute ischemic stroke, Young patients, Hyperhomocysteinemia